THE INFLUENCE OF STUDENTS LEARNING STYLE AND LEARNING INTEREST ON THE LEARNING OUTCOMES OF PHYSICS CLASS X IPA DURING THE COVID-19 PANDEMIC - Albert Lumbu; Bonefasius Y Boy; Muhamad Akbar (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2021)
This study aims to determine whether there are: 1) the influence of learning styles on physics learning outcomes, 2) the influence of interest in learning on physics learning outcomes, 3) the influence of learning styles and interest in learning together on physics learning outcomes in class X SMA Negeri 1 Nimboran . This research was conducted at SMA Negeri 1 Nimboran in April - May 2021. The subjects in this study were all 52 students of class X majoring in science and the objects of research were learning styles, interest in learning and physics learning outcomes. The instruments used are questionnaires and documentation. Data analysis was carried out using the Pearson correlation test with a significance level of 0.05 and a regression test which resulted in conclusions as a result of the study. The results showed that, 1) there was a significant influence of learning style on physics learning outcomes with a contribution of 50.8%, 2) there was a significant influence of interest in learning on physics learning outcomes with a contribution of 60.9%, 3) there were significant influence of learning style and interest in learning, together on the learning outcomes of physics with a contribution of 64.3% influence